Low-temperature flue gas denitration with transition metal oxides supported on biomass char. Issue 4 (August 2019) - Yang, Jie; Zhou, Jian; Tong, Wei; Zhang, Tianshi; Kong, Ming; Ren, Shan
Abstract: Several transition metals (Mn, Ce, V and Fe) were loaded on nitric acid modified biomass char (BC) using an impregnation method for the selective catalytic reduction (SCR) of NO with NH3 at low-temperature. The series of prepared catalysts were characterized by BET, SEM, FT-IR and XRD. Results showed the sequence of NO conversion within the temperature of 125–225 °C was Mn/BC > Ce/BC > V/BC > Fe/BC > BC, and Mn/BC exhibited the highest NO conversion of 87.6% at 200 °C. BC supports provided high surface area, which could contribute to the better dispersion of transition oxides on biomass char, revealing rich oxygen containing groups. Besides, the BC worked not only as a promising support, but also provided high activity adsorption sites for NH3 and conducted as oxidizing agent for NO due to the existence of graphite crystallite structure. Owing to the existence of "fast SCR" reaction process, the transition metal oxides supported on BC catalysts exhibited superior denitration efficiency in low temperature. Highlights: Transition metal oxides supported on BC showed high denitration efficiency. Nitric acid treatment could increase surface oxygen containing groups of BC. Biomass char conducted as oxidizing agent for NO.